Importance of motivation and work pay of young employees in the value creation chain of a business company: assessment of changes in and formation of expectations - Pilukienė, Laura (Business, Management and Economics Engineering, 2017)
As business companies compete in the market and seek to acquire a competitive advantage, one of the most important factors is well-motivated employees who are satisfied with their job. The success of companies operating in various sectors is determined by the quality of products, while the quality is ensured by qualified employees having appropriate skills and knowledge, whose work should be appreciated by monetary work pay established based on reasonable and clear criteria as well as other means of motivation. The process of human resources management in a business company places an ever-growing importance on the development of competences of employees, strengthening of cooperation, empowerment of employees as well as their work pay and motivation in order to achieve an employee’s work quality and productivity, satisfaction of customer needs and successful operation of a company. In the process of the company’s human resources management, special focus should be given to the satisfaction of the expectations and needs of new employees (who are usually young and inexperienced) as well as their integration, which ensures the generation of new and creative ideas in the company and, at the same time, high quality of products and work productivity.